2020
DOI: 10.3390/app10217674
|View full text |Cite
|
Sign up to set email alerts
|

How Can Nanoplastics Affect the Survival, Reproduction, and Behaviour of the Soil Model Enchytraeus crypticus?

Abstract: Nanoplastics (NPls) are ubiquitous in terrestrial environments, with numerous consequences for biodiversity and ecosystems. Research is urgently required to clarify the NPls environmental behaviour, fate and ecotoxicological effects to soil ecosystems. The aim of this research was to assess and comprehend the effects of polystyrene NPls to the terrestrial species Enchytraeus crypticus using survival, reproduction and avoidance behaviour as endpoints. A range of concentrations, 0.015 to 1500 mg NPls/kg LUFA 2.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Despite the few studies available involving E. crypticus and polystyrene-based NPls [11,30], one study showed that NPls (mean diameter: 60 nm) induced no effects in organisms' survival or reproduction at concentrations from 0.015 to 900 mg/kg [11]. The previous study is in accordance with the findings of the current study (absence of effects of NPls).…”
Section: Enchytraeus Crypticus Response To Contaminant Single Exposuressupporting
confidence: 91%
See 3 more Smart Citations
“…Despite the few studies available involving E. crypticus and polystyrene-based NPls [11,30], one study showed that NPls (mean diameter: 60 nm) induced no effects in organisms' survival or reproduction at concentrations from 0.015 to 900 mg/kg [11]. The previous study is in accordance with the findings of the current study (absence of effects of NPls).…”
Section: Enchytraeus Crypticus Response To Contaminant Single Exposuressupporting
confidence: 91%
“…Soil spiking was performed according to the following experimental conditions: single exposures of NPls (1.5 and 300 mg/kg) and DPH, AgNO 3 and VNPs (10 and 50 mg/kg), as well as the binary mixtures of NPls with each co-contaminant (1.5 mg NPls/kg + 10 mg DPH/kg; 1.5 mg NPls/kg + 50 mg DPH/kg; 300 mg NPls/kg + 10 mg DPH/kg; 300 mg NPls/kg + 50 mg DPH/kg; 1.5 mg NPls/kg + 10 mg AgNO 3 /kg; 1.5 mg NPls/kg + 50 mg AgNO 3 /kg; 300 mg NPls/kg + 10 mg AgNO 3 /kg; 300 mg NPls/kg + 50 mg AgNO 3 /kg; 1.5 mg NPls/kg + 10 mg VNPs/kg; 1.5 mg NPls/kg + 50 mg VNPs/kg; 300 mg NPls/kg + 10 mg VNPs/kg; 300 mg NPls/kg + 50 mg VNPs/kg). The selected single VNPs, AgNO 3 and NPls concentrations, the toxicities of which were previously studied [10,11,25], were used to examine the role of NPls in the toxicity of those contaminants. For DPH concentrations, its effects on E. crypticus were not known yet (single and combined with NPls).…”
Section: Test Soil and Spiking Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessing multigenerational effects allows us to understand the full impact of contaminants on populations over time as many contaminants can have long-lasting effects that are not immediately apparent [9]. Indeed, some studies have reported no significant effects on the survival and reproduction of terrestrial invertebrate species such as Folsomia candida [10] and Enchytraeus crypticus [11] after 28 and 21 days (d) NPls exposure, respectively. Therefore, it is essential to determine whether the absence of effects observed in a standard reproduction test persists through subsequent generations.…”
Section: Introductionmentioning
confidence: 99%